2014
DOI: 10.1002/art.38408
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum C‐Reactive Protein Levels With Lupus Disease Activity in the Absence of Measurable Interferon‐α and a C‐Reactive Protein Gene Variant

Abstract: Objective. The type I interferon (IFN) system is important in the pathogenesis of systemic lupus erythematosus (SLE).We previously demonstrated an inhibitory effect of IFN␣ on interleukin-6 (IL-6)-induced C-reactive protein (CRP) in vitro, hypothetically explaining the poor correlation between disease activity and CRP levels in SLE. This study was undertaken to investigate disease activity, IL-6 levels, and CRP levels in relation to a CRP gene polymorphism and IFN␣.Methods. Sera from 155 SLE patients and 100 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 49 publications
(70 reference statements)
2
26
1
Order By: Relevance
“…Moreover, although serum levels of CRP usually go in parallel with the disease activity in inflammatory states, the results from this point in SLE are inconclusive, being suggested that this autoimmune disease could be an exception (50). In this regard, while some authors have reported moderate levels of CRP (2.1 mg/l) in lupus subjects (51), others have associated this pathology with a high increase (15-16 mg/l) in this acute-phase protein (12). The reasons for this disparity are not entirely clear, however, disease exacerbation could be a determinant factor in this situation.…”
Section: Discusionmentioning
confidence: 99%
“…Moreover, although serum levels of CRP usually go in parallel with the disease activity in inflammatory states, the results from this point in SLE are inconclusive, being suggested that this autoimmune disease could be an exception (50). In this regard, while some authors have reported moderate levels of CRP (2.1 mg/l) in lupus subjects (51), others have associated this pathology with a high increase (15-16 mg/l) in this acute-phase protein (12). The reasons for this disparity are not entirely clear, however, disease exacerbation could be a determinant factor in this situation.…”
Section: Discusionmentioning
confidence: 99%
“…The biological consequences of IFNα that have been implicated in the pathogenesis of lupus have recently been reviewed in detail [121] and include the facilitation of antigen presentation via increased upregulation of class I and II major histocompability complex (MHC), maturation of dendritic cells and stimulation of B cells to become antibody producing plasma cells [122,123]. Although far from all SLE patients have measurable IFNα in serum [124,125], the majority present with increased expression of type I IFN regulated genes, the "type I IFN signature" [126]. [113].…”
Section: Ifnαmentioning
confidence: 99%
“…drug induced lupus [127,128]. Serum levels of IFNα (and/or a presence of type I IFN signature) also correlate with SLE disease activity, and are associated with presence of anti-dsDNA antibodies, nephritis, symptoms from the central nervous system, and hematological manifestations [124,125,129,130]. In addition, GWAS of SLE has revealed a major influence of single nucleotide polymorphisms (SNPs) of IFNα-related genes, such as IRF5, IRF7, IRF8 and STAT4 [12].…”
Section: Introductionmentioning
confidence: 99%
“…SLE disease activity index-2K), no single biomarker has yet been found to accurately mirror inflammation in each affected organ system [19]. C-reactive protein (CRP) which is frequently used to monitor systemic inflammation in various other conditions, is unfortunately not a reliable read-out of inflammation in SLE or viral infections, most likely due to an IFNα-dependent inhibition of hepatocyte CRP production [20,21]. Another clinical challenge in SLE is to conveniently discriminate ongoing disease activity from irreversible organ damage.…”
Section: Introductionmentioning
confidence: 99%